De la collection Fontana à la collection Spitzner, l’aventure des cires anatomiques de Paris à Montpellier - Hélène Palouzié; Caroline Ducourau (In Situ)
Associated with the medical school of Paris and held today by the University of Montpellier, the two most prestigious collections of wax medical models, the Fontana collection and the Spitzner collection, contribute to the history of artistic and scientific treasures, and feature the works of the most famous wax sculptors from the eighteenth century up to the twentieth: Fontana, Susini, Laumonnier, Baretta, Talrich, Tramond... They are objects of memory mobilising two complementary logics, that of their preservation in situ and that of their presentation as museum pieces. These initiatives have been initiated by the protection of the two collections as historic monuments.